Global Goods and the Spanish Empire, 1492-1824 Circulation, Resistance and Diversity - Aram, B.; Yun-Casalilla, B.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Drawing upon economic history, cultural studies, intellectual history and the history of science and medicine, this collection of case studies examines the transatlantic transfer and transformation of goods and ideas, with particular emphasis on their reception in Europe.
Keywords: History; Imperialism; Europe—History.; Social history; Civilization—History.; History, Modern; History of Science; Imperialism and Colonialism; European History; Social History; Cultural History; Modern History